How Efforts to Develop the Experts and Manpower Professional in Indonesia - Menara Simanjuntak; Haryadi Sarjono (Bina Nusantara University, 2011)
Development experts and skilled professionals in Indonesia is still needed today. This paper highlights the development efforts of experts and professionals in the Indonesia's executive power, as well as scientific studies which could give input for the government or educational institutions and industry. The approach used in this paper is library study by exploring the relevant references to the topic, and performed descriptive analysis. Institutions, such as universities and secondary vocational schools, are expected to produce skilled professionals with specific competence requirements. It is expected the government to prioritize opportunities to those less educated to follow a course skills, because they are the largest part of today's workforce. The weakness today is still a lot of educational institutions that do not have adequate infrastructure according to the requirements specified. The important conclusion is that the government is expected to give impetus and greater responsibility for higher education institutions, vocational schools and training centers and courses of work skills. In addition to the certification body to work more effectively because many Indonesian workers within and outside the country who do not yet have certification.